Bringing civility back in: reflections on global civil society - Anheier, Helmut K. (Development dialogue, 2007)
The debate on global civil society has become very conceptual and over-focused on the issue of definitions relative to empirical research findings. At the same time, there is a need to evaluate the contribu-tions of empirical studies of global civil society thus far, and to make
Gesehen am 24.10.2019